2008
DOI: 10.1021/ja801816k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Characterization of the HDV Genomic Ribozyme: Solvent Isotope Effects and Proton Inventories in the Absence of Divalent Metal Ions Support C75 as the General Acid

Abstract: The hepatitis delta virus (HDV) ribozyme uses the nucleobase C75 and a hydrated Mg(2+) ion as the general acid-base catalysts in phosphodiester bond cleavage at physiological salt. A mechanistic framework has been advanced that involves one Mg(2+)-independent and two Mg(2+)-dependent channels. The rate-pH profile for wild-type (WT) ribozyme in the Mg(2+)-free channel is inverted relative to the fully Mg(2+)-dependent channel, with each having a near-neutral pKa. Inversion of the rate-pH profile was used as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
119
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(140 citation statements)
references
References 69 publications
21
119
0
Order By: Relevance
“…pH titrations were conducted in the NMR tube, and the pH of the solution was measured using an ISFET micro pH probe (IQ Scientific Instruments) at the temperature of the titration. We previously reported that ion-dependent effects for this probe result in errors in measurement of pH for certain solutions (32). The effects of potassium ions on pH meter readings were therefore examined.…”
Section: Methodsmentioning
confidence: 99%
“…pH titrations were conducted in the NMR tube, and the pH of the solution was measured using an ISFET micro pH probe (IQ Scientific Instruments) at the temperature of the titration. We previously reported that ion-dependent effects for this probe result in errors in measurement of pH for certain solutions (32). The effects of potassium ions on pH meter readings were therefore examined.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to numerous studies of self-cleavage by the cisacting genomic and antigenomic HDV ribozymes (Been and Wickham 1997;Perrotta et al 1999aPerrotta et al ,b, 2006Wadkins et al 1999;Nakano et al 2000Nakano et al , 2003Shih and Been 2002;Harris et al 2004;Been 2006;Chadalavada et al 2007;Gong et al 2007Gong et al , 2009Sefcikova et al 2007a,b;Cerrone-Szakal et al 2008;Gong et al 2008;Chen et al 2009), significant work has also been performed to investigate trans-acting forms of this ribozyme for enzymology and therapeutic purposes (Been 1994;Luptak et al 2001;Harris et al 2002;Pereira et al 2002;Jeong et al 2003;Tinsley et al 2003Tinsley et al , 2004Das and Piccirilli 2005;Tinsley and Walter 2007;Walter and Perumal 2009). Generally, trans-acting HDV ribozymes exhibit a 1-2 order-of-magnitude slower catalytic rate constant compared to their cis-acting counterparts, likely due to a less tightly knit structure (Tinsley and Walter 2007).…”
Section: Introductionmentioning
confidence: 99%
“…4.3). 46,70,71 For the majority of studies conducted on the HDV ribozymes, the active-site cytosine could be assigned a proton-transferring role as either an acid or a base. However, three experiments strongly implied that the nucleobase acts as a general acid in the mechanism.…”
mentioning
confidence: 99%
“…35,36 Third, the rate of self-scission in the absence of Mg 2þ results in a pH profile and a kinetic solvent-isotope effect that support transfer from a protonated cytosine. 46,49,[71][72][73] Kinetic pH profiles, proton inventory experiments, and Brønsted analysis indicated that at least one proton is transferred during the rate-limiting step of the reaction, most likely the one from a protonated C75/76 to the oxyanion leaving group of G1. 69,71,74 In order for the cytosine to efficiently transfer a proton to the 5 0 oxyanion leaving group, its pK a needs to be shifted from approximately 4.2 toward neutrality.…”
mentioning
confidence: 99%
See 1 more Smart Citation